Faktor – Faktor yang Mempengaruhi Pendapatan Peternak Ayam Ras Petelur Di Kecamatan Lareh Sago Halaban Kabupaten Lima 50 Kota - Andri Andri; R. Wati; A. Suresti (Universitas Andalas, 2011)
The research was conducted in the District 50 Kota because this District is one of the central City broiler production in the province of West Sumatra. The objective of this research was to determine factors - factors that influence income layer poultry farmer in sub District lareh Sago Halaban and contribution of layer poultry farms to household incomes laying chicken farmers. The method used in this study was a survey method. The population were laying chicken farmers in the sub District lareh Sago Halaban. Sampling was done by census method and respondents number was 56 people. To see the effect of economic and non-economic factors on household income laying chicken farmers in sub District lareh Sago Halaban used regression equations and the contribution of laying chicken farms to income quantitatively analyzed. The results showed that the average revenue per production period was Rp. 674.672,235,01. The results of the model prediction variables that significantly affect the revenue is the economic variable is the cost of seedlings, drug costs and the cost of transportation, while the non-economic variables are not affected significantly in laying chicken farm business in the sub District lareh Sago Halaban this. Laying chicken farm business in the District lareh Sago Halaban contributed 94,02% to the income of farming households and the remaining 5,98% from other revenue sources.